C16:0-Ceramide Signals Insulin Resistance - Hla, Timothy (Cell Metab, 2014)
A substantive literature has accumulated implicating sphingolipids, in particular ceramides, as mediators of insulin resistance in metabolic syndrome. Thanks to recent technical advances in mouse genetics and lipidomics, two independent laboratories identify the same sphingolipid, C16:0-ceramide, as principal mediator of obesity-related insulin resistance.